SUSTENTABILIDADE AMBIENTAL DE UNIDADES FAMILIARES NA COMUNIDADE RURAL DO NOVO PINHEIRO, GLÓRIA DE DOURADOS-MS - SOUZA, Jéssica Oliveira; ARO, Daniele Torres; SANTOS, Cleberton Correia; SANTOS, Cristiane Ferrari Bezerra (ANAIS DO ENIC, 2017)
-